Modification entropy of Kerr–Sen-like black hole in Lorentz-breaking bumblebee gravity - Tan, Xia; Wang, Cong; Yang, Shu-Zheng (Frontiers in Physics, 2024)
The Lorentz symmetry breaking theory not only affects the space–time background but also the dynamic behavior of bosons and fermions in curved space–time. Therefore, the Lorentz symmetry breaking theory will affect the quantum tunneling rate, Hawking temperature, black hole entropy, and other physical quantities of black holes. According to the modification of the space–time background and the modification of the particle dynamic equations, the quantum tunneling radiation of the Kerr–Sen-like black hole in bumblebee gravitational theory and its related contents are deeply studied. The research methods and a series of new results obtained in this paper are discussed. This makes the research methods and conclusions in this paper of more astrophysical significance and reference value.